The contribution of stress to the comorbidity of migraine and major depression: results from a prospective cohort study. Issue 3 (9th March 2013) - Swanson, Sonja A; Zeng, Yiye; Weeks, Murray; Colman, Ian
Abstract : Objectives: To assess how much the association between migraine and depression may be explained by various measures of stress. Design: National Population Health Survey is a prospective cohort study representative of the Canadian population. Eight years of follow-up time were used in the present analyses. Setting: Canadian adult population ages 18–64. Participants: 9288 participants. Outcome: Incident migraine and major depression. Results: Adjusting for sex and age, depression was predictive of incident migraine (HR: 1.62; 95% CI 1.03 to 2.53) and migraine was predictive of incident depression (HR: 1.55; 95% CI 1.15 to 2.08). However, adjusting for each assessed stressor (childhood trauma, recent marital problems, recent unemployment, recent household financial problems, work stress, chronic stress and change in social support) decreased this association, with chronic stress being a particularly strong predictor of outcomes. When adjusting for all stressors simultaneously, both associations were largely attenuated (depression–migraine HR: 1.30; 95% CI 0.80 to 2.10; migraine–depression HR: 1.19; 95% CI 0.86 to 1.66). Conclusions: Much of the apparent association between migraine and depression may be explained by stress.